The impact of obesity on ocular hemodynamics and choroidal thickness. - Tufek, Melek; Nalcacioglu, Pinar; Capraz, Mustafa; Varol, Kenan; Kaya, Ahmet Turan; Aydın, Nihat; Kara, Caner (Therapeutic Advances in Ophthalmology, 2023)
Background: Obesity affects microvascular structures. The effect of obesity on the ocular vascular system can be evaluated by changes in the choroidal thickness (CT) and retrobulbar blood flow (RBF). Objectives: To evaluate the CT and RBF parameters in obese patients with various body mass index (BMI) values and compare these parameters with normal weight, healthy subjects. Design: A prospective study. Methods: The study included 102 eyes of 102 female patients. Patients were divided into three groups according to BMI as group 1 with a BMI of 18.5–24.99 (n = 32), normal weight group; group 2 with a BMI of 30–34.99 (n = 35), as obese class I; and group 3 with a BMI of 35–39.99 (n = 35), as obese class II. The peak systolic velocity (PSV), end-diastolic velocity (EDV), resistive index, and pulsatility index values of the central retinal artery (CRA) and ophthalmic artery (OA) were evaluated with color Doppler ultrasonography. CT was measured at the subfoveal area and at 500-µm intervals nasal and temporal to the fovea up to a distance of 1500 µm by using the enhanced depth imaging technique of optical coherence tomography. Intraocular pressure (IOP) was measured with a Goldmann applanation tonometry. Results: There was a significant difference in IOP values within the groups with the highest values in group 3 (17.6 ± 2.1 mmHg) and the lowest in group 1 (12.4 ± 1.7 mmHg). The CT in groups 2 and 3 was found to be statistically significantly lower than that in group 1 at all measurement points (p < 0.001). There was a statistically significant negative correlation between CT at all measurement points and BMI (p < 0.001). The mean CRA PSV, EDV, and OA EDV values were statistically significantly lower in each obese group than those values in group 1 (p < 0.001). The OA PSV values were significantly lower in group 3 (36.5 ± 5.9 cm/s) than those in group 2 (43.8 ± 4 cm/s) and group 1 (44.6 ± 5.2 cm/s) (p < 0.001). Also, significant associations were found between BMI and CRA PSV, CRA EDV, and OA PSV values (p < 0.001). Conclusion: Obesity may predispose to eye pathologies by changing the ocular vascular circulation.